Low and Zero Prevalence Rates of Anti-measles Virus Immunoglobulin G in Mothers and Their Infants Respectively in Health Centers in Osogbo, Nigeria" (2014)
We undertook this study to determine the susceptibility of mother-infant pair participants to measles virus infection in two health centers in Osogbo, Osun State, Nigeria. This is a descriptive, cross-sectional hospital-based study. The study was carried out in Osogbo, southwestern, Nigeria between November, 2012 and February, 2013. With ethical approval and participants’ consents, 83 mothers and their 84 infants were consecutively recruited; blood samples were aseptically collected from them by thumb puncture onto Whatman filter paper. The papers were appropriately labeled; air-dried and kept in brown envelopes which we kept in clean polythene bags and stored at 4ºC until assayed. Freshly prepared PBS was used to elute serum from 5 to 6 punched-out disks from each Whatman filter paper. The supernatant from the spun eluate of each sample was assayed for anti-measles virus IgG using ELISA. Overall, 2.41% and zero percent seroprevalence rates were recorded from the nursing mothers and their infants respectively. We concluded that the seropositivity of anti-measles virus IgG antibody in the nursing mothers from the two health facilities was very low, and that all the infants and most (97.59%) of the nursing mothers were apparently susceptible to measles virus infection.